Crepuscular pollination and reproductive ecology of Trembleya laniflora (Melastomataceae), an endemic species in mountain rupestrian grasslands - Soares, Natalia Costa [UNESP]; Morellato, Leonor Patrícia Cerdeira [UNESP] (Elsevier, 2018)
The “pollination syndrome” hypothesis predicts a direct relationship between a set of floral characters and the principal pollinating agent. The presence of flowers with poricidal anthers, heterostemony and pollen as the only reward are common traits in Melastomataceae species and are associated with buzz pollination by bees. Trembleya laniflora Cong. (Melastomataceae: Microlicieae) is an endemic species from campo rupestre tropical grassland, with large and white “pollen flowers” differing from the common purple-colored flowers of the Tribe. We examine the relationship between the distinct floral characteristics of T. laniflora and its pollination syndrome and reproduction ecology. We observed different individuals of T. laniflora randomly sampled in Serra do Cipó Espinhaço Range, Minas Gerais, southeastern Brazil. We carried out observations on their reproductive phenology (31 individuals), flower biology (3), pollination (23), and tested the reproductive system (29). Trembleya laniflora presented a seasonal flowering pattern in the dry and post-dry seasons (May–October) and set fruits during the dry, post-dry and rainy seasons (June–December). Floral aperture occurred mainly during the night and the first hours of the morning, the period with the greatest availability of fresh flowers and with the highest visitation by Xylocopa bimaculata. Tests identified the species as non-apomictic, self-incompatible and dependent on large bees such as Xylocopa, Bombus, Centris and Ptiloglossa for pollination. Trembleya laniflora showed a specialized pollination system mediated by a restricted group of bees that perform crepuscular buzz pollination. Floral characteristics and reproductive biology of T. laniflora are likely adaptive responses to pollination by large bees foraging during the crepuscular hours. Our results support the “pollination syndrome” hypothesis, demonstrating a direct relationship between a set of floral characters and the principal pollinators of the species. Dependence on interbreeding may promote outcrossing within and among the endemic populations, naturally isolated on rocky outcrops.
Keywords: Buzz pollination; Floral traits; Germination; Nocturnal bees; Phenology; Reproductive system